ICSH: on board for new projects. (June 2014) - Zini, G.; Kern, W.; Brereton, M.; Stephens, A. D.; ,
Summary The International Council for Standardization in Hematology (ICSH) is a not‐for‐profit organization aimed at improving global quality and harmonization of analytical methods, and achieving reliable and reproducible results in diagnostic hematology. ICSH co‐ordinates Working Groups of experts to examine laboratory methods and instruments for hematological analyses, and co‐operates with different international organizations which have similar scientific goals. Among seven ongoing approved projects, three ICSH projects have been selected and will be presented in the ICSH session at the XXVIIth ISLH International Symposium on Technological Innovations in Laboratory Hematology in The Hague, on May 2014. The project on 'Guideline for flow cytometric evaluation of patients with suspected acute myeloid leukemia (AML) and myelodysplastic syndromes (MDS)' covers different aspects of the application of immunophenotyping by multiparameter flow cytometry (MFC) in the diagnosis of AML and MDS including integration into multimodal diagnostic workflow, quality control, antibody selection, interpretation of findings, reporting, and personnel. Data from the pilot study of the project for 'International Standardization of Hematology Reporting Units' suggest that there is a wide variation in reporting units for the routine blood cell count and highlights the areas of nomenclature and units of measurement where standardization is necessary and feasible, such as units for cell counts, white cell differentials, and hemoglobin concentration. The project on 'Standardization of HbA2 measurement and its implications for clinical practice' starts from the observation that different instruments give different results for hemoglobin A2; it is aimed at producing recommendations as to how instrument manufacturers and laboratories should assess their equipment before using it to analyze patient samples. These projects are examples of how the ICSH represents a great opportunity for scientists involved in hematology laboratory to participate in a process of expert collaboration and discussion all around the world.